Enhancing the Skills of Mate Jaklou Pokmaswas in Raja Ampat Through Literacy Training - Dayu Rifanto; Jajat S Ardiwinata; Joni Rahmat Pramudia; Hans Agung Pasak; Tri Kurnia Goram; Zakarias Magari (Yayasan Keluarga Guru Mandiri, 2025)
This study evaluates the effectiveness of literacy training for Pokmaswas in the Raja Ampat region, especially in North and East Misool, using a pre-experimental method with a one-group pretest-posttest design. The main focus is improving literacy and conservation awareness among Pokmaswas members and teachers. Quantitative data were collected through pre-test and post-test, while qualitative data were obtained through in-depth interviews. The results showed a significant increase in understanding among participants, with the average score rising from 30 to 48.94 at Pos Kasim and from 34.16 to 54.16 at Pos Fol Pulau in Folley Island. Most participants achieved